SLC11A1 is expressed in the human placenta across multiple gestational ages. (January 2019) - Perry, Ian D.; Krishnan, Lakshmi; Murphy, Shawn P.
Abstract: The human placenta functions as an innate immune barrier to prevent fetal infection. However, the molecular mechanisms accounting for placental resistance to pathogens are currently poorly understood. The solute carrier family 11 member 1 (SLC11A1) is a divalent cation transporter expressed primarily by macrophages and neutrophils that is essential for controlling infections by intracellular pathogens such as Salmonella, Leishmania and Mycobacteria. This report demonstrates that SLC11A1 is expressed in the syncytiotrophoblast of the human placenta at multiple gestational ages. These results suggest that SLC11A1 may play a role in blocking productive placental infections by certain intracellular pathogens. Highlights: Solute carrier family 11 member 1 (SLC11A1) is expressed in the human placenta. SLC11A1 expression is localized to the syncytiotrophoblast at multiple gestational ages. SLC11A1 may prevent infection of the placenta by certain intracellular pathogens.